Steroid-responsive encephalopathy in autoimmune thyroiditis: Clinical spectrum and MRI observations in three cases - K Dinkar; Sanjib Sinha; A B Taly; P S Bindu; R D Bharath (Annals of Indian Academy of Neurology, 2011)
Hashimoto′s encephalopathy (H.E.) is probably of autoimmune etiology, and manifests with seizures, stroke-like episodes, cognitive decline, neuropsychiatric symptoms, myoclonus. It is presumed to be autoimmune in origin with high serum titers of antithyroid peroxidase antibodies (anti-TPA). Thyroid function might often be normal. The diagnosis is arrived at by excluding other toxic, metabolic and infectious causes of encephalopathies, supportive clinical profile, elevated thyroid antibodies and optimum steroid response. We present the characteristic phenotypic manifestations, magnetic resonance imaging and electroechography observations and response to immunomodulation with follow-up in three cases of H.E. All the three cases manifested with subacute to chronic progressive encephalopathy, cerebellar dysfunction, seizures, behavioral abnormalities and oculomotor disturbances and had evidence of hypothyroidism, elevated titers of anti-TPA and positive thyroid anti-microsomal antibodies. Atypical and uncommon presentations are known. This report emphasizes that a high index of suspicion is often required in cases with "investigation negative encephalopathy" for early diagnosis of H.E.